Prospective Mathematics Teachers’ Critical Thinking Disposition in Designing Cognitive and Psychomotor Assessment Instruments - Kurniati, Dian; Trapsilasiwi, Dinawati; As'ari, Abdur Rahman; Basri, Hasan; Osman, Sharifah (Universitas Islam Negeri Raden Intan Lampung, 2022)
The disposition of critical thinking is one of the predictors of the success of prospective mathematics teachers in accustoming their students to critical thinking and mathematical literacy in responding to mathematical problems. Therefore, it is necessary to conduct research that focuses on the critical thinking disposition of prospective mathematics teachers in designing learning, including assessment instruments. The research aims to describe the critical thinking disposition of prospective mathematics teachers in designing cognitive and psychomotor assessment instruments to familiarize junior high school students with critical thinking and mathematical literacy. It was qualitative in nature, with an exploratory, descriptive methodology with 16 mathematics education students in the fifth semester of the Universitas Jember as research subjects. All research subjects attended three lectures on Evaluation of Mathematics Teaching and Learning Outcomes by applying a collaborative learning model based on team projects. The research findings have indicated that prospective mathematics teachers have a critical thinking disposition in compiling a project on cognitive and psychomotor assessment instruments based on the junior high school students critical thinking and mathematical literacy. The components of the critical thinking disposition of prospective mathematics teachers that emerged during three times lectures were truth-seeking, open-mindedness, maturity, and curiosity. Prospective mathematics teachers collaborated and cared about each other with friends in completing projects.